Blood propofol concentration and psychomotor effects on driving skills - Grant, S.A.; Murdoch, J.; Millar, K.; Kenny, G.N.C. (British journal of anaesthesia : BJA, 2000)
We studied psychomotor performance in 10 healthy volunteers during recovery after a target-controlled infusion of propofol. Choice reaction time, dual task tracking with secondary reaction time and a within-list recognition task were assessed at target blood propofol concentrations of 0.8, 0.4 and 0.2 μg ml−1. Performance was impaired most at the highest blood propofol concentration (choice reaction time increased by a mean of 247 ms and secondary reaction time by a mean of 178 ms). Choice reaction time and dual task tracking with secondary reaction time were the most sensitive and reliable methods of assessment (significant difference from baseline (P<0.05) at a propofol concentration of 0.2 μg ml−1 with choice and secondary reaction time testing). Within-list recognition assessment of memory was not sufficiently sensitive at very low propofol concentrations. The impairment in choice and secondary reaction time with a blood propofol concentration of 0.2 μg ml−1 was less than that observed with a blood alcohol concentration of 50 mg 100 ml−1 and no greater than that observed with a blood alcohol concentration of 20 mg 100 ml−1 in a previous study involving healthy volunteers.